Effect of calcination temperature on Ce/Opa catalyst in municipal plastics waste catalytic pyrolysis to fuel grade liquid product - Ruzinah, Isha; Wen, Loong Pui; Normardhati, Mustafa; Hafizah, Ramli; Rahimah, Ismail (Elsevier Ltd, 2022)
Catalytic pyrolysis of plastic polymers is becoming an increasingly important method for the conversion of plastic materials into valuable chemicals and oil products. The effect of calcination temperature on Cerium loaded on oil palm ash (Ce/OPA) catalyst and products in catalytic pyrolysis of HDPE plastic were studied and evaluated. The catalysts were synthesized via wet impregnation method. The catalyst was calcined at 500°C, 750°C and 1000°C. The catalysts were also characterized by using Scanning Electron Microscope (SEM) and Brunauer and Emmett and Teller (BET). The calcined catalyst was tested in laboratory batch reactor at 450 °C with 15mL/min N2 and 10:1 of plastic-to-catalyst weight ratio for one hour. The liquid products were analyzed via mass spectrometry GC-TCD, GC-MS, FTIR, bomb calorimeter and viscometer. It is found that Ce/OPA catalyst that calcined at 500 °C for four hours showed better catalytic pyrolysis activity and has largest specific surface area (10.77 m2 /g) than the catalyst that calcined at 750°C and 1000°C. The Ce/OPA that calcined at 500°C catalytic cracked the HDPE waste with less solid yield (25.2 wt.%) and more gas yield (18.40 wt. %). The liquid products with calorific value ranging from 50.34 MJ/kg– 50.39 MJ/kg and viscosity value between 1.06 cP-1.29 cP were also obtained. Moreover, the liquid product’s density ranging between 0.74 g/ml-0.78g/ml and clarity of 7.11 NTU - 52.30 NTU was achieved with diesel carbon range (C12-C24). In conclusion, the calcination temperature remarkably affected the catalytic activity of Ce/OPA and improved properties of products. The Ce/OPA catalyst has high potential to be used in catalytic plastic waste pyrolysis for a low-cost alternative fuel production. in Municipal Plastics Waste Catalytic Pyrolysis to Fuel Grade Liquid Product